2022
DOI: 10.3389/fphys.2021.779121
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Regulation of Muscle Mitochondria and Calcium Signaling by Insulin/IGF-1 Receptors Depends on FoxO Transcription Factors

Abstract: Insulin and IGF-1, acting through the insulin receptor (IR) and IGF-1 receptor (IGF1R), maintain muscle mass and mitochondrial function, at least part of which occurs via their action to regulate gene expression. Here, we show that while muscle-specific deletion of IR or IGF1R individually results in only modest changes in the muscle transcriptome, combined deletion of IR/IGF1R (MIGIRKO) altered > 3000 genes, including genes involved in mitochondrial dysfunction, fibrosis, cardiac hypertrophy, and pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…In TA, Ndufb8 protein was significantly increase in Aged TKO compared with all other groups whereas other subunits showed less change, but similar patterns to Quad (Figure S9d,e ). Transcriptional regulation of OXPHOS subunits by insulin action is mediated by FoxOs, 26 , 27 so we measured mRNA levels of several OXPHOS subunits in our young and aged groups. Ndufs2, Ndufb8, and Sdhb were significantly decreased in Aged Ctrl Quad when compared with Young Ctrl, but Aged TKO showed no changes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In TA, Ndufb8 protein was significantly increase in Aged TKO compared with all other groups whereas other subunits showed less change, but similar patterns to Quad (Figure S9d,e ). Transcriptional regulation of OXPHOS subunits by insulin action is mediated by FoxOs, 26 , 27 so we measured mRNA levels of several OXPHOS subunits in our young and aged groups. Ndufs2, Ndufb8, and Sdhb were significantly decreased in Aged Ctrl Quad when compared with Young Ctrl, but Aged TKO showed no changes.…”
Section: Resultsmentioning
confidence: 99%
“…This makes it difficult to fully assess the role of FoxOs in age‐related sarcopenia. This mild aging phenotype may be due to the mixed genetic background that we described in detail previously, 27 which is a major challenge when using mice to study aging‐related muscle defects. Nonetheless, we do see important decreases in max force generation that are prevented in Aged TKO, which is an important measure of muscle strength in aging.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…MAPK14, serine/threonine kinase which is one of the 4 p38 MAPKs, p38α MAPK14 is a circadian regulator [53] by phosphorylating various proteins, and it is reported that p38αMAPK inhibitor is efficacious in suppression of synaptic dysfunction in mouse models. [54] IGF1R is upstream of FOXO, [55] while knockdown of BCL2L11 (Bim) or BCL2L1 ectopic expression restrains FOXO3-mediated ROS overproduction and apoptosis. [56] CCL5, formerly known as Regulated on Activation, Normal T Cell Expressed and Presumably Secreted, is one of the CC subfamily of chemokines and plays a role in the peripheral immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt pathway was early proved involved in the anti-apoptotic effects of estrogen mediated by ER-α and ER-β in skeletal muscle cells, especially at the mitochondrial level ( 57 , 58 ). FoxO transcription factors are strongly implicated to multiple regulatory and signaling pathways of oxidative phosphorylation, inflammatory signaling, TCA cycle, and mitochondrial function ( 59 ). It was found that muscle atrophy could be ameliorated by regulating myostatin-mediated PI3K/Akt/FoxO3a pathway and satellite cell function in chronic kidney disease ( 60 ).…”
Section: Discussionmentioning
confidence: 99%